Does platelet indices play a role in the distinction of pulmonary embolism clinical forms? - Telo, Selda; Kırkıl, Gamze; Kaman, Dilara; Bulmuş, Funda Gülcü (My University, 2017)
Aim: The aim of this study is to investigate the changes in platelet indexes, including mean platelet volume (MPV), platelet distribution width (PDW) and platelet count (PC), in patients with acute pulmonary embolism (PE), in addition to evaluating the diagnostic value in clinical forms.Material and methods: The study consisted of 84 patients with PE and the control group consisted of 40 healthy subjects. PE patients were divided into two groups in accordance with the clinical forms as 60 submassive and 24 nonmassive. The differences in platelet count, MPV, PDW, PC, D-dimer, and other indicators were analyzed between the two groups. Venous peripheral blood samples to measure the MPV, PDW and PC were acquired on admission.Results: MPV levels were found to be statistically higher in the submassive group compared to the nonmassive group and the control group (p<0.01 and p<0.001, respectively). PDW levels were found to be statistically higher in the submassive group compared to the non-massive group and control group (p=0.027 and p<0.001, respectively). PC was significantly lower in the submassive group compared to the non-massive group and control group (p=0.022 and p<0.001, respectively). It was determined that a positive correlation existed between the MPV and right ventricular diameter (RVD) (r=0.27, p<0.01).Conclusion: High MPV and PDW levels and low PC may be indicators of the severity of acute PE. Also, the correlation between the MPV and RVD suggests that MPV can be used as a marker of right ventricular function.
Keywords: Solunum Sistemi; Genel ve Dahili Tıp; Patoloji; Hematoloji; Kalp ve Kalp Damar Sistemi